THE USE OF HUMOUR AS COMMUNICATION SKILL IN COUNSELLING AND PSYCHOTHERAPY - Oprea-Valentin BUȘU; Andreea-Denisa BUȘU (Universitaria Publishing House, Craiova, 2021)
Although humour has received a lot of attention when it comes to general psychological research due to its demonstrated positive effects on wellbeing and relationship maintenance, it appears to be disregarded in relation to Counselling and Psychotherapy training. To this date, there are no empirical studies focused on how counselling students use and view humour and there have been very few research endeavors aimed to study humour as a communication skill in Psychotherapy. This article explores the existing literature on the use of humour in counselling. Towards the end, it aims to answer whether or not humour should be taught in Psychotherapy training.